Female Football Players and Fans Intruding into a Man's World (Football Research in an Enlarged Europe, 2018)
This edited collection draws on social science approaches to provide insights into the world of women's football and female fans. Providing in-depth analysis of the development of the women's game in different European countries, it examines both the experiences of female fans of men's football and women's views, perceptions and evaluations of women's football. Female Football Players and Fans will be of interest to students and scholars in a range of fields, including sports sociology, sport sciences, gender studies, women's studies and fandom and cultural studies.